The impact of corporate governance mechanisms on risk management - Abdul Rashid, Aimi Zulhazmi; Zandi, GholamReza; Hui, Yao (Opción, 2019)
The main objective of this research is to identify and prioritize the corporate governance factors that have an influence on risk management and how they can be helpful to enrich risk management capabilities of Malaysian banks. The researcher employed both qualitative and quantitative research methods based on the nature of the research topic. As a result, the majority of employees are unable to assess whether the board had discharged their fiduciary and leadership functions. In conclusion, all commercial banks in Malaysia had adopted effective and strict application of the code of corporate governance and the most effective code is accountability.